2019
DOI: 10.4049/immunohorizons.1900026
|View full text |Cite
|
Sign up to set email alerts
|

CRP Induces NETosis in Heart Failure Patients with or without Diabetes

Abstract: C-reactive protein (CRP) is recognized as a biomarker of chronic, low-grade inflammation associated with vascular disorders. Lately, the role of neutrophils and neutrophil extracellular traps (NETs) has been investigated as a potential source of chronic inflammation and cardiovascular complications. This study investigated NETs as a marker of inflammation in patients with symptomatic heart failure (HF) with or without type 2 diabetes (T2DM) and examined the correlation between NETs and CRP. We performed a noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 56 publications
3
24
0
1
Order By: Relevance
“…More recently, we and other groups reported elevated levels of circulating NETs in T2DM patients and an increase in their neutrophil capacity in vitro to release NETs (15,43,44). Furthermore, we observed an increase in circulating NETs and corresponding release in HF patients, the latter reaching a maximum in HF + T2DM (15). The results from this study con rm that NETs release is signi cantly increased in clinical HF and more so in patients with HF and T2DM.…”
Section: Nets Release From Human Neutrophilssupporting
confidence: 83%
See 1 more Smart Citation
“…More recently, we and other groups reported elevated levels of circulating NETs in T2DM patients and an increase in their neutrophil capacity in vitro to release NETs (15,43,44). Furthermore, we observed an increase in circulating NETs and corresponding release in HF patients, the latter reaching a maximum in HF + T2DM (15). The results from this study con rm that NETs release is signi cantly increased in clinical HF and more so in patients with HF and T2DM.…”
Section: Nets Release From Human Neutrophilssupporting
confidence: 83%
“…Heart failure (HF) is a pro-in ammatory condition, in which the magnitude of in ammation is associated with the disease severity, being maximal in acute decompensated heart failure (ADHF) patients. Lately, we and other groups reported an increase of NETs formation, either circulating or under in vitro neutrophil stimulation in type 2 diabetic (T2DM) patients (13)(14)(15) and in patients suffering from HF with or without T2DM (15). HF classi cation is based on left ventricular ejection fraction (LVEF), which can be reduced (HFrEF, LVEF ≤ 40%) or preserved (HFpEF, LVEF ≥ 50%), each with distinct phenotypes (16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was also demonstrated that plasma CRP were inversely associated with FEV1 22 . Furthermore, it was shown that CRP induces a concentration-dependent NET synthesis 23 . A possible hypothesis can be that impaired lung function leads to a systemic inflammation with elevated CRP level which induces NETosis.…”
Section: Discussionmentioning
confidence: 99%
“…NET release can be triggered by various inflammatory mediators found elevated in severe COVID-19, including CRP, IL-1β, IL-6 and IL-8 [50]. There is also a positive correlation between circulating serum of IL-6, IL-8, CRP and NET levels [60]. NETs are found in a variety of conditions such as infection, malignancy, atherosclerosis, and autoimmune diseases with reports now emerging that describe their presence in COVID-19 [9,[61][62][63].…”
Section: Plos Computational Biologymentioning
confidence: 96%